PENGARUH FILM FILOSOFI KOPI 2: BEN & JODY TERHADAP MINAT BERBISNIS COFFEE SHOP DI KALANGAN BARISTA KOTA PEKANBARU - Herdianto "; Ismandianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research aims to determine how much effect the Filosofi Kopi 2 : Ben & Jody film on the interest in doing coffee shop business among barista’s in Pekanbaru City. The research method used is quantitative explanation with the positivism paradigm with the theoretical model used namely S-O-R (Stimulus – Organism – Response) theory. Researcher must be objective by first testing wheter the limitations of the concept and measuring instrument have met the standards of realibility and validity. Meanwhile, the explanation is intended to explain the generalization of the sample to the population or to explaint the differences and effect of a variable with others. The population in this study is the barista’s spread across 104 coffee shop in Pekanbaru City. The sampling technique in this study using accidental sampling (samples from easy to find people) and the guest have watched Filosofi Kopi 2: Ben & Jody film, with a total of 50 respondents. Data collection technique in this study used a questionnaire and documentation. The data in this study were measured on a likert scale. Data analysis performed was descriptive analysis, simple linear regression, data normality test and coefficient of determination.The result of the study based on the significance value is 0,000 which is smaller than the probability of 0,05, meaning that Ho is reject and Ha is accepted, which means there is a significant effect between Filosofi Kopi 2 : Ben & Jody film on the interest in doing coffee shop business among barista’s in Pekanbaru City. The linear regression equation obtained is Y=1,025 + 0,944 X. Meanwhile, based on coefficient of determination (R2) test of 0,646. Means the independent variable (Film) has an effect proportion of 64,6% on the dependent  variabel (interest). Keywords : effect film, coffee shop, barista, the interest in doing business